Deregulation, franchising, outsourcing and corporatisation in local public transport: International experience - Graham Currie (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2016)
This paper explores the experience of developed countries that have introduced greater private sector involvement to traditionally government owned and run urban public transport industries. Such reforms have generally been driven by a desire to reduce taxpayer costs and to improve services for travellers. Reform options of full open competition, alternative tendering models and negotiated performance based contracting are considered. Just as the possible models for reform are diverse, so too have been the outcomes from reforms across different contexts. Case studies from bus reforms in the UK and rail and tram reforms in Melbourne, Australia provide several lessons for other jurisdictions considering reforms in urban public transport. In particular, the evidence suggests that cost savings and service improvements are achievable through corporatisation of public agencies and the introduction of service tendering, though savings tend to be once-off and are subject to excessive optimism. Caution is also urged in the introduction of open competition in markets that are not commercially viable. Performance based contracts that involve arm's length cooperation between the government and operator, when combined with the threat of competition, can achieve a good balance between the desire for quality and network flexibility from government with the commercial imperatives of the operator.
Keywords: 330; Kommunale Verkehrspolitik; Öffentlicher Nahverkehr; Deregulierung; Großbritannien; Australien